The Highest Oxidation State of Rhodium: Rhodium(VII) in [RhO3]+. Issue 38 (10th August 2022) - da Silva Santos, Mayara; Stüker, Tony; Flach, Max; Ablyasova, Olesya S.; Timm, Martin; von Issendorff, Bernd; Hirsch, Konstantin; Zamudio‐Bayer, Vicente; Riedel, Sebastian; Lau, J. Tobias
Abstract: Although the highest possible oxidation states of all transition elements are rare, they are not only of fundamental interest but also relevant as potentially strong oxidizing agents. In general, the highest oxidation states are found in the electron‐rich late transition elements of groups 7–9 of the periodic table. Rhodium is the first element of the 4d transition metal series for which the highest known oxidation state does not equal its group number of 9, but reaches only a significantly lower value of +6 in exceptional cases. Higher oxidation states of rhodium have remained elusive so far. In a combined mass spectrometry, X‐ray absorption spectroscopy, and quantum‐chemical study of gas‐phase R h O n + ( n =1–4), we identify R h O 3 + as the 1 A 1 ' trioxidorhodium(VII) cation, the first chemical species to contain rhodium in the +7 oxidation state, which is the third‐highest oxidation state experimentally verified among all elements in the periodic table. Abstract : Teaming up with technetium and ruthenium, rhodium is the third element of the 4d series to form the rare +7 oxidation state, the third‐highest oxidation state among all elements. Here, gas‐phase X‐ray absorption spectroscopy, combined with quantum‐chemical calculations, are used to elucidate RhO 3 + as a 1 A 1 ' trioxido rhodium(VII) cation in D 3 h point group symmetry, the first chemical species with rhodium in the +7 oxidation state.